Biochemical and Structural Characteristics, Gene Regulation, Physiological, Pathological and Clinical Features of Lipocalin-Type Prostaglandin D2 Synthase as a Multifunctional Lipocalin - Urade, Yoshihiro (Frontiers in Physiology, 2021)
Lipocalin-type prostaglandin (PG) D2 synthase (L-PGDS) is the first member of the lipocalin family recognized as an enzyme. PGD2 stimulates Gs-coupled DP receptors involved in the regulation of sleep, pain, food intake etc.; Gi-coupled CRTH2 receptors, in myelination of peripheral nervous system, adipocyte differentiation and inhibition of hair follicle neogenesis, etc.; and Gq-coupled FP receptors, in dexamethasone-induced cardioprotection. L-PGDS is the same protein as -trace, the most abundant protein in human cerebrospinal fluid produced in the brain, and distributed in the central nervous system and male genital organs of various mammals, and human heart; and is secreted into the cerebrospinal fluid, seminal plasma, and plasma, respectively. L-PGDS binds retinoic acids and retinal with high affinities (Kd <100 nM) and diverse small lipophilic substances, such as thyroids, gangliosides, bilirubin and biliverdine, heme, NAD(P)H, etc. L-PGDS also binds amyloid  peptides, prevents their fibril formation, and disaggregates amyloid  fibrils, acting as a major amyloid  chaperone in human cerebrospinal fluid. Here, I summarize the recent progress of the L-PGDS research, in terms of its “molecular properties”, “cell culture studies”, “animal experiments” and “clinical studies”, all of which should help to understand the pathophysiological role of L-PGDS and inspire the future research of this multifunctional lipocalin.